The Context of Public Policy on the Sharing Economy - Błażej Koczetkow; Andrzej Klimczuk (The Sharing Economy in Europe: Developments, Practices, and Contradictions, 2022)
The purpose of this chapter is to analyse approaches to the sharing economy from the perspective of public policy science. In the first part of the text, attention is paid to perceiving the development of the emerging sharing economy not only as phenomenon with positive economic effects but also as a set of public problems (e.g., on the labour market and for existing economic structures) that require intervention at the level of national governments as well as at international level. Subsequent sections identify possible actions for regulating the development of the sharing economy. The role of soft law, stakeholders' networks, self-regulation and standardisation are discussed in the chapter. The summary includes potential directions for further research.
Keywords: D16; L86; Z18; Z13; 330; Informal tools of regulation; Public policy instruments; Regulations and the sharing economy; Self-regulation in the sharing economy; Soft law; Standards in sharing economy